Searching for Uniqueness and its Relationship to Perfectionism among the Lecturers of College of Education for Human Sciences - Sha’ban Hassan , Assist. Lect . Hassan (Basra studies journal, 2025)
current research mission aims at identidying the following: the search for uniqueness and perfectionism among permanent members of the mention college staff members. The two research tools were applied to the comprehensive creativity of 100 males and females instroctors from the College of Education for Humanities at the University of Basra. The results of the search revealed that there is a direct positive relationship between the search for uniqueness and the perfection of the luxury of the research sample.